Textbook Elucidation: An Analysis of Thematic Structure and Progression on the Ministry of Education and Culture Grade X English Textbook Revision Edition - Thauransyah Ghofur Ismail; Agus Rofi'i; Rama Dwika Herdiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
An instructional material becomes one of the most crucial factors in determining the success of learning process. Textbook as one of the kind of instructional materials poses its vital role in assisting teachers in the learning process. Acting as a cohesive device in discourse analysis, thematic structure and progression pattern analysis have been popularly used in analyzing texts’ theme-rheme structure and its deployment pattern. This study centered on analyzing the theme rheme structure and progression patterns on some specific reading texts. A grade X english textbook endorsed by Ministry of Education and Culture has been chosen to be the object of analysis. Out of 17 existing passages within the textbook, author has purposively selected three reading texts with different genre to be the data of the research. To begin the investigation, each of the selected text was broke down into clauses and then analyzed the theme and rheme within each clause. Progression patterns analysis was done by analyzing the deployment pattern of themes and rhemes within the texts. The investigation uncovered unmarked themes on single clause level became the most dominating theme among others. The themes showed up 61 times and occupied 44.53% of all themes occurrences. At the bottom two rarest theme occurrences are marked and interpersonal themes with a percentage of 2.94% and 0.74%. Ultimately, concerning the cohesiveness of the text, all four progression patterns occurred within the text and 166 items of cohesive devices indicating reference & repetition were found well-distributed in all three texts.